The influence of a concurrent cognitive task on lower limb reaction time among stroke survivors with right- or left-hemiplegia. Issue 5 (October 2015) - Pauley, Tim; Phadke, Chetan P.; Kassam, Adam; Ismail, Farooq; Boulias, Chris; Devlin, Michael
Abstract : Objective: To determine the impact of cognitive interference on foot pedal reaction time among stroke survivors with right- (RH) or left-hemiplegia (LH). Design: Cross-sectional comparison without randomization. Subjects/patients: 10 patients post-stroke with RH, 10 with LH; 10 age-matched controls. Methods: Foot pedal response times were measured using three different reaction time (RT) paradigms: simple RT, dual-task RT (counting backward by serial 3 seconds), and choice RT (correct response contingent on stimuli to eliminate pre-programing). RH and LH used the non-paretic leg for all trials. Three 3 (RT task) × 3 (group) mixed-model factorial ANOVAs were used to compare RT, movement time (MT), total response time (TRT). Results: Overall controls demonstrated faster RT than RH (332 ± 73 versus 474 ± 144 ms, P < 0.001) or LH (402 ± 127 ms, P < 0.05); LH group demonstrated faster RT than those with RH ( P < 0.05). Control subjects demonstrated significantly faster RT than RH for all RT conditions ( P < 0.05 for all). In contrast, controls achieved significantly faster RT than LH for the choice RT condition only ( P < 0.05), but not for the simple ( P = 0.12) or dual-task RT conditions ( P = 0.25). Conclusions: Compared to controls, response time was significantly impaired among LH and RH when the response could not be pre-programmed. While current simple RT testing commonly employed by driver rehab specialists may be sufficient for detecting RT deficits in patients with RH, simple or dual-task RT tests alone may fail to detect RT deficiencies among LH, even when testing the non-paretic limb. Choice RT should be added to post-stroke driver fitness assessment, particularly for patients with LH.